Knowledge, Attitude and Practices of Medical and Dental House Officers for the Prevention of Hepatitis B and C in the Hospital Setting - Maira Tasleem, Maria Khawaja, Sheharbano Manzoor, Amna Nauman Khan, Sarah Rabbani, Nauman Rauf Khan (Pakistan Journal of Medical & Health Sciences, 2022)
The aims of our study are to determine the knowledge, attitude and practices of hepatitis B and C among house officers. A structured self-administered questionnaire was used to check out the knowledge, attitude, and practices towards personal protective measures taken by house officers to prevent hepatitis B and C. We used a pre-testified questionnaire used before for the examination of Hepatitis B and C. A total of 150 house officers were included in the study wa a mean age of 22.5 ± 0.082 years. Almost all the house officers 146 (97.3%) heard about hepatitis B virus infection. half of the house officers 79 (52.7%) never participated in health education program. The present study showed that house officers have good knowledge about the gravity of the disease but lacks the deep information specially regarding its transmission and preventive measures.